The importance of homework in the system of mathematical education - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2023)
The article examines the factors that describe homework policy and characterize their influence on students’ achievements in learning mathematics. The data of national research of 2004 is analyzed on the basis of statistic methods. 346 mathematics teachers and 2030 students of the 6th form and 1827 students of the 10th form took part in the research. Most teachers recognize that the main function of homework is to review the knowledge and skills acquired in the classroom. However, the results of the research show that this object is achievable in case students are responsibly trained for homework, and the teacher develops the right students’ attitude towards their duties by constant and moderate insistence.